Distribution of rare earth elements and yttrium in water, suspended matter and bottom sediments in Lake Onego: Evidence of the watershed transformation in the Late Pleistocene. (20th January 2023) - Strakhovenko, Vera; Belkina, Natalia; Subetto, Dmitry; Rybalko, Alexander; Efremenko, Natalia; Kulik, Natalia; Potakhin, Maxim; Zobkov, Mikhail; Ovdina, Ekaterina; Ludikova, Anna
Abstract: Data on the mineralogy and geochemistry of rare earth elements (REE + Y) in water, suspended matter and stratified sediment cores from different parts of Lake Onego are presented. The study finds that the dissolved REE + Y in the water from different areas of Lake Onego have common features: (1) a maximum in the area of middle rare earth elements (MREE), (2) a distinct negative Ce anomaly and (3) a positive Eu anomaly. Comparison of the average concentration of elements in the stratified core of the bottom sediments and particulate matter (from the filters and sedimentation traps) from different parts of Lake Onego and the distribution of REE + Y do not reveal any significant differences. The trend of the REE + Y distribution for samples from the South Onego completely coincide the REE + Y distribution in siltstones and sandstones of the Russian Platform Scale Composite (RPSC). In the water area of Lake Onego from south to north, a well-defined trend of changes in REE + Y patterns relative to the RPSC is revealed, with depletion by heavy REE + Y and gradual enrichment by light rare earth elements (LREE). Geochemical and mineralogical data confirm our hypothesis of a significant reformatting of the catchment basin of the Onego Ice Lake in the Late Pleistocene. During the formation of the preglacial lake, a significant part of the catchment area was located south of Lake Onego and is mainly represented by Russian Platform sedimentary rocks. Due to the degradation of the Last Glacier from the Lake Onego depression and the nearby territories, the catchment area changed of its southern and south-eastern sections. Today the composition of the modern sedimentary matter entering Lake Onego is determined by mixing clusters from two geochemically contrasting feeding areas: loose sediments formed by the repeatedly re-deposited products of the weathering of the Fennoscandian Shield's crystalline rock massifs, including Phanerozoic sediments; and to a lesser extent the sediments of the sedimentary cover of the Russian Platform, except the bottom sediments of the South Onego, in which Phanerozoic sedimentary formations have completely predominated throughout the lake's development.